Pengkajian Penerapan Prinsip Iktikad Tidak Baik dalam Pendaftaran Merek pada Sengketa Merek “C+Logo” - Lucia Samosir; Rika Ratna Permata; Aam Suryamah (Jurnal Hukum dan Sosial Politik, 2025)
The advancement of information technology has driven the growth of the creative industry, which heavily relies on intellectual works, one of which is trademarks as part of the Intellectual Property Rights regime. A trademark not only serves as a product identity but also as a marketing tool and a determinant of reputation. However, in practice, legal issues often arise, particularly related to the registration of trademarks by parties acting in bad faith and having substantial similarities with previously registered trademarks. This research analyzes the Application of the Principle of Bad Faith in the trademark registration process in the trademark dispute "C+Logo" between Gunawan and PT Bagava Alam Semesta. Through descriptive analysis research with a normative juridical approach, the results of this study indicate a violation of the principle of bad faith in the trademark registration conducted by PT Bagava Alam Semesta because it meets the principle of bad faith violation as examined in accordance with the Trademark and Geographical Indications Law.